Role of water oxidation in the photoreduction of graphene oxide. Issue 12 (23rd January 2019) - Li, Hongjiang; Song, Xuedan; Shi, Yantao; Gao, Yan; Si, Duanhui; Hao, Ce
Abstract : By means of a H2 18 O labeling experiment in combination with mass spectrometry tracking, we studied GO photoreduction. Abstract : By means of a H2 18 O labeling experiment in combination with mass spectrometry tracking, we studied GO photoreduction. Observation of 18 O labeled O2 provides direct evidence to confirm that water oxidation occurs during GO photoreduction. In combination with DFT calculations, we propose a mechanism for O2 and CO2 evolution in the photoreduction of GO.